Three-dimensional analysis of perineural invasion in extrahepatic cholangiocarcinoma using tissue clearing - Hirokazu Ogasawara; Hirokazu Ogasawara; Tadashi Yoshizawa; Kiyoko Oshima; Kenta Ogasawara; Kenta Ogasawara; Shunsuke Kubota; Shunsuke Kubota; Shintaro Goto; Satoko Morohashi; Taiichi Wakiya; Norihisa Kimura; et al. (Frontiers Media S.A., 2023)
Perineural invasion (PNI) is a characteristic invasion pattern of distal cholangiocarcinoma (DCC). Conventional histopathologic examination is a challenging approach to analyze the spatial relationship between cancer and neural tissue in full-thickness bile duct specimens. Therefore, we used a tissue clearing method to examine PNI in DCC with three-dimensional (3D) structural analysis. The immunolabeling-enabled 3D imaging of solvent-cleared organs method was performed to examine 20 DCC specimens from five patients and 8 non-neoplastic bile duct specimens from two controls. The bile duct epithelium and neural tissue were labeled with CK19 and S100 antibodies, respectively. Two-dimensional hematoxylin/eosin staining revealed only PNI around thick nerve fibers in the deep layer of the bile duct, whereas PNI was not identified in the superficial layer. 3D analysis revealed that the parts of DCC closer to the mucosa exhibited more nerves than the normal bile duct. The nerve fibers were continuously branched and connected with thick nerve fibers in the deep layer of the bile duct. DCC formed a tubular structure invading from the epithelium and extending around thin nerve fibers in the superficial layer. DCC exhibited continuous infiltration around the thick nerve fibers in the deep layer. This is the first study using a tissue clearing method to examine the PNI of DCC, providing new insights into the underlying mechanisms.